PTEN and PI3K mutation markers and expression of CD68 and IL-6 inflammatory markers in endometrioid and clear cell ovarian carcinoma with underlying endometriosis - Arsad N; Abd Aziz NH; Tizen Laim NMS; Md Zin RR; Abdul Hafizz AMH; Mohamad Nasir Shafiee (Penerbit Universiti Kebangsaan Malaysia, 2024)
The objective of this research endeavour was to ascertain whether there existed a distinction in the protein expression levels of phosphatase and tensin homolog (PTEN), phosphatidylinositol-4,5-biphosphate3-kinase (PI3K), macrophage (CD68), and interleukin-6 (IL-6) among women who had been diagnosed as having ovarian carcinoma (endometrioid and clear cell subtypes) underlying endometriosis. Tissue microarray (TMA) slides were fabricated using donor’s formalin-fixed paraffinembedded (FFPE) blocks that comprised specimens of ovarian carcinomas tissues with the subtypes of endometrioid and clear cell that were retrieved for a duration of nine years. A total of 19 FFPE blocks represented 19 cases of carcinoma of the ovary, which were categorised into two groups: ovarian cancer with endometriosis (EAOC, n=10) and ovarian cancer without endometriosis (n=9). All of these protein expressions were analysed using immunohistochemistry (IHC) technique. Following that, comparisons were made regarding the clinical and pathological characteristics of the ovarian carcinomas, as well as any discernible variations in expression levels between the two groups. In EAOC, PTEN expression was lower (88.9% vs. 100%, P=0.47) compared to those without endometriosis. Our findings revealed an increase of PI3K and IL-6 in EAOC than those devoid of endometriosis; 80% vs. 77.8%, P=1.00 and 70% vs 11.11%, P=0.35, respectively. In contrast, CD68 was significantly lower in endometriosis-associated ovarian cancer compared to those without endometriosis (40% vs. 66.67%, P=0.16). In conclusion, there were no significant difference in the mutational and inflammatory marker modifications between clear cell carcinoma and endometrioid adenocarcinoma of ovary with endometriosis.